The Effect Of Project Based Learning Model On Students Learning Outcomes In 5 Grade Thematic Learning At SDN 24 Batangase Maros - Nurhikma Sari (International Journal of Elementary School Teacher, 2022)
This research is an experimental research type with a quantitative approach. This study aims to describe the application of the project-based learning model to the thematic learning for class V at SDN 24 Batangase Maros, and to describe student learning outcomes in thematic learning for class V students at SDN 24 Batangase Maros. The population of this study were fifth grade students at SDN 24 Batangase Maros with a total population of 92 students consisting of 3 classes. The sample in this study were students of class VB AND VC with a total of 59 students. Data collection techniques in this research are observation, test and documentation. After the data is collected then the processing is carried out by statistical analysis and inferential statistics with the help of IBM SPSS version 26. The results of the descriptive analysis show that the average value of learning outcomes in the experimental class before using project based learning (pre-test) is 35.83, which means it is at poor category, while the average score of students after implementing the project based learning strategy (post-test) was 69.17 which was in the good category. Furthermore, the average value of student learning outcomes in the control class that was not treated without applying the project based learning model (pre-test) was 35.69 which was in the less category while the average value was not treated without applying project based learning (post-test). ) is 53.28 which is in the sufficient category. Based on the results of these studies, there is a positive effect of the application of the project based learning model on learning outcomes in the thematic learning of fifth grade students at SDN 24 Batangase Maros.